Best Practice Examples of Implementing Ecosystem-Based Natural Hazard Risk Management in the GreenRisk4ALPs Pilot Action Regions - Beguš, Jurij; Berger, Frédéric; Kleemayr, Karl (IntechOpen, 2021)
One of the best ways to improve collective knowledge and practice is through sharing experiences and knowledge between different stakeholders. The idea for the current monograph followed such an approach. The monograph presents six best practice examples from six of the project's Pilot Action Regions (PAR). It is one of the deliverables of the GreenRisk4ALPs project funded by the EU Interreg Alpine Space program. The project aims to develop decision support tools supporting risk-based protective forest management in the Alpine Space. All main outputs of the project have been tested, improved and operationally applied in the PARs. The monograph is primarily intended for forestry experts, decision-makers at all levels of decision-making and other professionals.